The Philippines : Options for FInancing Energy Efficiency in Public Buildings - World Bank Group (World Bank, Washington, DC, 2018)
The primary objective of this project was to identify options for addressing barriers to financing, for scaling up EE implementation in public buildings in the Philippines. Section two of this report provides a summary of the available data on public buildings, including the energy consumption characteristics of government buildings and facilities, estimates of the potential for energy savings, and investments needed. Section three discusses some of the barriers to financing EE that has been seen in other countries, and summarizes such barriers in the public sector in the Philippines, including legal and regulatory barriers; lack of access to commercial financing; institutional barriers; and limited implementation capacity. Section four provides information about international experience in the financing of public sector EE projects. It includes a review of six different financing mechanisms: budget financing; EE revolving funds; dedicated EE credit lines; risk-sharing programs; public or super ESCOs; and commercial financing using ESCOs and performance contracting. It also presents a comparative assessment of the key characteristics of each of these financing options. Section five identifies three options that are considered appropriate for implementation in the Philippines, budget financing, an EE revolving fund, and a public or super ESCO, and provides detailed information on each. It also presents information on the potential role of international financial institutions in providing complementary financial and technical assistance. Section six summarizes the advantages and limitations of the three proposed financing options; presents the World Bank’s recommendations; and provides guidance on moving forward with the development of a national program.